STRATEGI PENINGKATAN STATUS AKREDITASI RUMAH SAKIT DI RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN KEPULAUAN MERANTI - ", M. Anrian; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Based on the Regulation of the Health Minister of the Republic Indonesia Number 012 Year 2012 about Hospital Accreditation, Hospital are required to follow the national accreditation in order to increase the competitiveness and quality of hospital services. Currently district general hospital Meranti islands still not getting accreditation status. Strategy to increase hospital accreditation status are the steps that have been planned and implemented in a district general hospital Meranti islands to obtain the status of hospital accreditation. The research aims to determine how the strategy to increase the status of accreditation and factors that affect the strategy set by the Meranti Islands Regency General Hospital. The author uses SWOT (Strengths, Weaknesses, Oppurtunities, Threats). This study used a qualitative descriptive approach using key informan methods with data collecting technique using interviews, observation, and documentation. Results of this research is the Strategy to Increase Hospital Accreditation Status in Regional General Hospital (Hospital) Meranti Islands Regency has not been effective this is because the Meranti Islands Regency General Hospital has not been able to optimize the strengths and opportunities of the hospital. Factors affecting among other things: Quality and Quantity of Human Resources, Budget Planning, Monitoring and Socialization Accreditation and Standard Operating Procedure (SOP). Keywords: Strategy, Hospital Accreditation. Regional General Hospital (RSUD)